Strategy for soil protection in cross-border region of Hungary and Romania - Lazányi, János; Demeter, Gábor (Applied Studies in Agribusiness and Commerce, 2011)
Within the Hungary-Romania Cross-Border Co-operation Programme for 2007-2013 the University of Debrecen and the University of Oradea is to elaborate a soil strategy for the Nyírség and Bihor Mts region. Project partners expect the strategy will support and strenghten national, regional and local soil policies and contribute to the competitiveness of the region by protecting and developing various soil functions. Project partners also expect to prevent cross-border problems with soil and reduce the competition caused by cost differences.The elaboration of the strategy includes the problems of erosion, deflation, compaction, water-deficiency, inland water-threat, problems induced by the usage of fertilizers, loss and substitution of soil organic matter, amelioration (bentonite, sewage sludge, fermented biogas). Based on summarised data of former examinations and new experiments a concise database will make it possible to calculate and apply the Sustainability Index Model, which may be useful in order to address EU supports properly based on objective calculations, and may be useful to determine the optimal culture. The project also encourages the farmers to keep in mind the cross-compliance, since EU gives financial support to realise sustainable soil strategy based on EU directives. This may enhance the options to initiate the take off of rural areas with shrinking export facilities, to mitigate social tensions and the effect of migration processes.